Global business workforce restructuring : labour and employment law and benefits : issues raised by restructuring, mergers, sales, acquisitions, and redundancies /: labour and employment law and benefits : issues raised by restructuring, mergers, sales, acquisitions, and redundancies. (2003) - Unknown
No abstract available